Перспективы развития страхового рынка Украины - Колпакова, Н.С. (Культура народов Причерноморья, 2013)
В статье рассмотрены основные проблемы развития страхового рынка в Украине, проведен анализ основных тенденций, происходящих на страховом рынке, осуществлен анализ концентрации страхового рынка Украины по основным типам страховых компаний, изучены проблемы перестрахования, выявлены факторы, влияющие на его развитие, намечены основные направления и перспективы дальнейшего изменения и развития рынка страхования в Украине. Ключевые слова: рынок, страхование, перестрахование, факторы развития У статті розглянуті основні проблеми розвитку страхового ринку в Україні, проведений аналіз основних тенденцій, що відбуваються на страховому ринку, здійснено аналіз концентрації страхового ринку України за основними типами страхових компаній, досліджені проблеми перестрахування, встановлені чинники, що впливають на його розвиток, визначені основні напрямки та перспективи подальших змін та розвитку ринку страхування в Україні. Ключові слова: ринок, страхування, перестрахування, фактори розвитку The challenges and prospects for the development of insurance market in Ukraine were given in the article and theoretical foundations of the functioning of the insurance market was analysed. The latest publications of this problem was carefully work out. The author analyzed the major trends occurring in the insurance market and carried out analysis of the concentration of it in Ukraine on the main types of insurance companies. Dynamics of changes in the volume of foreign capital in the authorized capital of insurers, estimated their assets in Ukraine were defined, also outlook of changes was carried. We studied the problem of reinsurance, factors that influence its development, the analysis of the cost of risk insurance in finding Ukrainian citizens abroad in the context of tourism and other departures, including the most popular countries. The author studied the formation of net premiums and payments, and the level of net interest payments as a percentage in dynamics. Based on these researches outlined the main directions and prospects for change and development of the insurance market in Ukraine. Established that the modern insurance market in its development has certain achievements and numerous shortcomings of the functioning of individual insurance companies and insurance in general. Keywords: market, insurance, reinsurance, factors of development